Characterisation of ion bunches by a single-pass non-destructive charge counter. Issue 24 (January 2020) - Kiffer, M; Ringleb, S; Stallkamp, N; Kumar, S; Arndt, B; Vogel, M; Quint, W; Stöhlker, Th
Synopsis: We present non-destructive single-pass ion bunch detection and characterisation by measuring the induced image charge in a detection electrode. The presented technique allows direct determination of ion kinetic energy, absolute ion number and spatial ion bunch length. We will show the results of corresponding measurements with bunches of low-energy highly charged ions and discuss the minimum detectable number of charges.